Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/1933719116654989
|View full text |Cite
|
Sign up to set email alerts
|

Slug Is Associated With Tumor Metastasis and Angiogenesis in Ovarian Cancer

Abstract: Ovarian cancer is the most lethal gynecologic malignancy among women and usually initiated by the malignant transformation of epithelial cells. The progression of ovarian cancer involves a cascade of events, including tumor cell epithelial-mesenchymal transition (EMT), invasion, migration, and angiogenesis. Slug plays vital roles in the development of motile and invasive manner of cancer cells via EMT progression. The present work is devoted to investigate the effect of slug on the invasion and angiogenesis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Among them, Slug is closely associated with tumor metastasis in ovarian cancer [28]. In the present study, Slug has identified specific mechanisms controlled during EMT in the A2780 and SK-OV-3 cells.…”
Section: Discussionmentioning
confidence: 65%
“…Among them, Slug is closely associated with tumor metastasis in ovarian cancer [28]. In the present study, Slug has identified specific mechanisms controlled during EMT in the A2780 and SK-OV-3 cells.…”
Section: Discussionmentioning
confidence: 65%
“…It is well established that Slug is a key transcription factor implicated in angiogenesis and the EndoMT transition by repressing E-Cad expression and inducing N-Cad expression, thereby effectively regulating the transition between EMT and MET [38,39]. Slug has been reported to be overexpressed in many types of cancer, including lung cancer [40][41][42][43][44][45][46]. In addition, it is known that the family of EMT-TFs can be activated by a myriad of receptors and signaling pathways including tumor growth factor TFGβ, Notch, Wnt, morphogenetic protein BMPs, Ras/Erk pathways as well as inflammation, hypoxia and shear stress forces, and that the EMT-TF can also regulate each other in complex and interdependent ways [12,47].…”
Section: Discussionmentioning
confidence: 99%
“…EMT-related transcription factors play important roles in cancer dissemination. Previous studies indicate that many of these factors, including TWIST 18 , SLUG 19 , and β-catenin 20 , act synergistically and reciprocally with one another and use common pathways (reviewed in 21 ), which are associated with poor prognosis of EOC. Then we conducted immunofluorescence (IF) staining to examine whether CRS affected expression of these factors in tumor tissues.…”
Section: Crs Facilitates Metastasis Of Epithelial Ovarian Cancer In Nmentioning
confidence: 99%